IEEE e-Science 2009: presentations from the conference - Oxford e-Research Centre (Oxford e-Research Centre, 2009)
Presentations from IEEE sponsored workshop on e-Science applications, tools and methods. See http://ora.ouls.ox.ac.uk/objects/uuid:af1a6da7-5826-4cf3-9a59-d1de7d8b8389 for other collections from this conference.